HUBUNGAN PENERAPAN ISO 9001: 2000 DAN ORGANISASI PEMBELAJAR TERHADAP KINERJA STAF (Studi di Lembaga P2PNFI Regional I Jayagiri dan P2PNFI Regional II Semarang ) - Retnowati, Elais; Trisnamansyah, Sutaryat (JURNAL TADRIS STAIN PAMEKASAN, 2010)
Abstract: This research is based on facts of the implementation of ISO 9001:2000 at P2PNFI Region I Jayagiri and P2PNFI Region II Semarang in a few years, to find out whether the implementation of ISO 9001:2000 gives an impact in building a learning organization as the creation of the lifelong learning as well as the performance of two institutions which based on ISO. This research used the expost facto method and based on the correlation approach.  The design of development strategies on this research are: (1) conducting the beginning study; (2) creating research instruments; (3) testing instruments; (4) analyzing the validity and reliability instruments; (5) distributing questioners to 94 respondents at P2PNFI Regional I Jayagiri and 84 respondents at P2PNFI Regional II Semarang; (6) collecting questioners; (7) data input and processing; (8) conducting data analyzing and (9) wrapping up the conclusion. The research reveals that (1) there is a high relationship between the implementation of ISO 9001:2000 with the staf performance; (2) there is a high relationship between the learning organization with the staf performance and (3) there is a high relationship between the implementation of ISO9001:2000 and the learning organization with the performance of staf at two institutions. (4) there is an increase of the staf performance.